Minocycline and magnesium in combination attenuates oxidative stress and decreases ischemic neuronal damage in vivo - Bhattacharya P.; Pandey A.K.; Paul S. (My University, 2025)
A neuroprotective strategy through a combination therapy is always being superior to any other singular therapeutic interventions, as these acts through a multifaceted approach within the brain during focal cerebral ischemia. Therefore, the development of a potential new combination of drug which can bring about desirable improved neuroprotection targeting different pathways against ischemic stroke is necessitated. Numerous past studies have enumerated the neuroprotective roles of minocycline and magnesium administered in single against focal ischemia in animal model, hence we hypothesized that by using magnesium with minocycline in combination would provide additive neuroprotection than either of the agents used alone. To test this hypothesis, we subjected adult male rats to anesthesia and administered them with magnesium and minocycline in single standard dose and then standard doses in combination consequently at 5 minutes after creating focal ischemia by transient middle cerebral artery occlusion with 24 h of reperfusion. The animals were allowed to recover for 5 days before undergoing neurological score after focal ischemia. Following sacrificed, histological and biochemical examination for neuroprotection was carried out and it was observed that a significant greater neuroprotection was rendered by the group administered with a combination dose of minocycline (10 mg/kg) and magnesium (40 mg/kg) in respect to the groups administered the dose in singlet.